Fat and bone in children - where are we now? - Paul Dimitri (Korean Society of Pediatric Endocrinology, 2018)
The risk of fracture secondary to low-impact trauma is greater in obese children, suggesting obese children are at risk of skeletal fragility. However, despite this finding, there is a lack of agreement about the impact of excessive adiposity on skeletal development. The combination of poor diet, sedentary lifestyle, greater force generated on impact through falls, and greater propensity to falls may in part explain the increased risk of fracture in obese children. To date, evidence suggests that in early childhood years, obesity confers a structural advantage to the developing skeleton. However, in time, this relationship attenuates and then reverses, such that there is a critical period during skeletal development when obesity has a detrimental effect on skeletal structure and strength. Fat mass may be important to the developing cortical and trabecular bone compartments, provided that gains in fat mass are not excessive. However, when fat accumulation reaches excessive levels, unfavorable metabolic changes may impede skeletal development. Evidence from studies examining bone microstructure suggests skeletal adaption to excessive load fails, and bone strength is relatively diminished in relation to body size in obese children. Mechanisms that may explain these changes include changes in the hormonal environment, particularly in relation to alterations in adipokines and fat distribution. Given the concomitant rise in the prevalence of childhood obesity and fractures, as well as adult osteoporosis, further work is required to understand the relationship between obesity and skeletal development.